A long trip into the universe: Psychedelics and space travel - Lerer, Leonard; Varia, Jeet (Frontiers in Space Technologies, 2022)
Prolonged periods in space have potentially deleterious physiological and psychological effects. Ensuring the physical health and mental well-being of astronauts will inevitably supersede the need for technological innovation, as the major challenge in long-duration space travel. We propose a role for psychedelics (psychoactive fungal, plant, and animal molecules that cause alterations in perception, mood, behavior, and consciousness) and in particular psychedelic mushrooms to facilitate extended sojourns in space. Psychedelics research is in the midst of a renaissance and psychedelics are being explored not only for their therapeutic potential in psychiatry, but also for their ability to promote neuroplasticity, modulate the immune system and reduce inflammation. Psychedelics may be to long-duration space travel in the 21st century, what citrus fruits were to long-distance sea travel in the 18th century – breakthrough and facilitatory. The human intergalactic experience is just beginning and it would be wise to consider the benefits of ensuring that astronauts undertaking potentially perilous space voyages benefit from our planet’s rich psychedelic heritage. There is also some justification for considering the application of psychedelics in the processing and integration of the profound and spiritual experience of deep space travel.